Relationship between achievement motivation, trait anxiety and self-esteem - Aktop, A.; Erman, K. A. (Biology of Sport, 2006)
The purpose of present study was to investigate relationship between achievement motivation, trait anxiety, and self-esteem. Furthermore, secondary aim of study was to determine achievement motivation, trait anxiety and self-esteem level of athletes, which are attained sport in different level. One hundred seventy five male engage in sport active, were a Student in Akdeniz University School of Physical Education and Sport, aged from 18 to 25 years (21.90±1.87 yr.) participated the study voluntarily. Willis Sport Related Motive Scale, Rosenberg Seif Esteem Scale and Spielberger's Trait Anxiety Inventory were applied to subjects. As a result of correlation analysis, it was found that there was a significant positive correlation between power motive, motive to achieve success and self-esteem and there was a significant negative correlation between trait anxiety and self esteem. Comparison analysis according to sport experiences level showed that; there were significant differences in favour of high sport experiences group in power motive, motive to achieve success and self-esteem (p<0.05). It was found that self-esteem and trait anxiety value of subject were related significantly (r=0.28). Self-esteem was affected by sport experiences level and subjects who were in high experiences group had higher self-esteem value than the other groups (p<0.05). Results indicate that self-esteem is an important trait for achieving success in sport. According to these fmdings, psychological factors should be considered as much as other factors in talent identification programs. Furthermore, achievement motivation and self-esteem are importänt trait having permanent character for sport attainment and success.